The Role of Trust in Mediating the Impact of Electronic Word of Mouth and Security on Cryptocurrency Purchase Decisions - Muhamad Irfan (Bright Institute, 2024)
This study investigated the role of trust (TR) in mediating the impact of electronic word of mouth (EW) and security (SE) on cryptocurrency purchase decisions (PD). A cross-sectional survey design was employed, and data were collected through 330 distributed questionnaires, of which 320 valid responses were retained after validation steps that included confirming prior cryptocurrency usage. The sample consisted of active cryptocurrency users in Indonesia, aiming to explore the relationships between EW, SE, attitudes (AT), perceived behavioral control (PB), TR, and PD. Structural equation modeling was used to analyze the data and test the hypothesized relationships. The findings highlighted that TR significantly mediated the effects of both EW and SE on PD, underscoring TR as a crucial factor in the cryptocurrency market. Additionally, the study revealed that PB played a significant role, particularly in mediating the relationship between SE and PD, suggesting that consumers' confidence in managing transactions greatly influences their purchasing behavior. The results contribute to the literature by validating an integrated model that combines key factors influencing cryptocurrency PD and extending the Theory of Planned Behavior by incorporating EW and SE as antecedents. The study provides practical implications for cryptocurrency platforms and marketers, emphasizing the need for robust security measures, positive EW management, and user-friendly interfaces to foster TR and enhance consumer engagement in the cryptocurrency market.